Syrians' Awareness of Cardiovascular Disease Risk Factors and Warning Signs: A Cross Sectional Study - Sarya Swed; Hidar Alibrahim; Haidara Bohsas; Mohammed Amir Rais; Sheikh Shoib; Anas Alali; Mohamed Abdelnasser; Hadeel Fuad Alwan Alsharjabi; Bisher Sawaf (International Journal of Medical Students, 2022)
Background: An estimated 17.8 million lives were lost in 2017 due to cardiovascular disease (CVD), resulting in a total of 330 million years of life lost and an additional 35.6 million years of disability. Numerous studies have shown the importance of education and awareness in promoting positive and long-lasting behavioral changes. This study aims to assess Syrians' awareness of cardiovascular disease (CVD) warning symptoms and risk factors and investigate further into the variables that contribute to this awareness.